Evaluasi Sistem Proteksi Penangkal Petir pada Bangunan Power House Bandara Sams Sepinggan - Andriani, Dewi Safira (MASALIQ, 2024)
The aim of this research is to solve the lightning protection system (which has been installed and to determine the effectiveness of the lightning protection system. In this research the evaluation method is carried out using data collection and data analysis methods. Data collection methods consist of, observation, measurement, literature study, and Interview. Data analysis consists of, Building needs for lightning protection, Determining protection, Distribution conductors, and Grounding. The evaluation results show that, based on the index stated in the standard (SNI 037014.1-2004) the Main Power House building really needs a lightning protection system. Based on the estimated danger of lightning strikes with a risk level of R=14 (highly recommended), the use of conventional lightning rods with the protection angle method still requires increased protection in the form of the addition of 5 air terminations (splitzers) on the right, left, front, side and back. and the distribution conductor and earth termination (grounding) for both lightning rods as a whole meet the standards.